Metaverse innovation in public service transformation in Makassar metropolitan city - Ramli, Muhammad; Mahmud, Akilah (Universitas Islam Negeri Alauddin Makassar, 2023)
Metaverse is one of the innovations that can be used in various types of activities without the need to meet in the same room, just through virtual space that can be widely operated. This study aims to 1) analyze forms of metaverse-based public service innovation, 2) analyze opportunities and challenges in implementing metaverse-based public service innovations in Makassar Metropolitan City, 3) analyze government efforts made in implementing public service innovations based on metaverse in Makassar Metropolitan City. The research method used is based on descriptive qualitative by observing and collecting data from previous researchers as well as conducting direct interviews with several parties concerned. Based on the results of the research, it shows that the Makassar city government has shown strong efforts, including adopting policies and regulations that support the implementation of metaverse-based public services. In addition, the provision of infrastructure, campaigns related to metaverse education, collaboration with the private sector and academia, as well as procuring a pilot project as an implementation of the effectiveness of using metaverse-based public services.